(untitled) (Biodiversitas Journal of Biological Diversity, 2016)
Mollaei-Darabi S, Kooch Y, Hosseini SM. 2014. Reaction and fractal description of soil bio-indicator to human disturbance in lowland forests of Iran. Biodiversitas 15: 60-66. Earthworms are expected to be good bio-indicators for forest site quality. The deforestation of land into another function could changes the soil features that could effect on earthworm population. This study was conducted to understand the changes of soil functions, resulting from exploitive management using some soil features and their fractal dimensions. Two sites were selected, consisting of an undisturbed forest site (DS) in lowland part of Khanikan forests located in Mazandaran province, north of Iran. Within each site 50 soil samples were obtained from 0-30cm depth along two sampling lines with 250 meter length for each. Deforestation brought a lower soil quality in the sites under the study. Decreasing silt, clay, moisture, pH, carbon to nitrogen ratio, available Ca, earthworm density and biomass, increasing bulk density and sand were few outcomes of the deforestation. Except for clay, the deforestation affect on fractal dimension of soil features. The fractal dimension of bulk density, silt, moisture, pH, earthworm density and biomass were decreased imposed by deforestation. Our results suggest that deforestation should be regarded as an effective factor on variability of soil features that are tied to forest ecology. This is significant for evaluating forest management policies and practices with respect to effects on soil and also for the use of soils as indicators, especially earthworms as bio-indicator, of forest ecosystems.